Estimates of genetic parameters for growth traits in Brahman cattle using random regression and multitrait models - Bertipaglia, T. S. [UNESP]; Carreño, L. O.D. [UNESP]; Aspilcueta-Borquis, R. R. [UNESP]; Boligon, A. A.; Farah, M. M. [UNESP]; Gomes, F. J. [UNESP]; Machado, C. H.C.; Rey, F. S.B. [UNESP]; da Fonseca, R. [UNESP] (Oxford University Press (OUP), 2015)
Random regression models (RRM) and multitrait models (MTM) were used to estimate genetic parameters for growth traits in Brazilian Brahman cattle and to compare the estimated breeding values obtained by these 2 methodologies. For RRM, 78,641 weight records taken between 60 and 550 d of age from 16,204 cattle were analyzed, and for MTM, the analysis consisted of 17,385 weight records taken at the same ages from 12,925 cattle. All models included the fixed effects of contemporary group and the additive genetic, maternal genetic, and animal permanent environmental effects and the quadratic effect of age at calving (AAC) as covariate. For RRM, the AAC was nested in the animal’s age class. The best RRM considered cubic polynomials and the residual variance heterogeneity (5 levels). For MTM, the weights were adjusted for standard ages. For RRM, additive heritability estimates ranged from 0.42 to 0.75, and for MTM, the estimates ranged from 0.44 to 0.72 for both models at 60, 120, 205, 365, and 550 d of age. The maximum maternal heritability estimate (0.08) was at 140 d for RRM, but for MTM, it was highest at weaning (0.09). The magnitude of the genetic correlations was generally from moderate to high. The RRM adequately modeled changes in variance or covariance with age, and provided there was sufficient number of samples, increased accuracy in the estimation of the genetic parameters can be expected. Correlation of bull classifications were different in both methods and at all the ages evaluated, especially at high selection intensities, which could affect the response to selection.
Keywords: Covariance functions; Genetic correlation; Heritability; Maternal effects; Selection